2019
DOI: 10.3390/ijerph16091481
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Environmental Contamination and Estimated Radiation Exposure Dose Rates among Residents Immediately after Returning Home to Tomioka Town, Fukushima Prefecture

Abstract: On 1 April 2017, six years have passed since the Fukushima Daiichi Nuclear Power Station (FDNPS) accident, and the Japanese government declared that some residents who lived in Tomioka Town, Fukushima Prefecture could return to their homes. We evaluated environmental contamination and radiation exposure dose rates due to artificial radionuclides in the livelihood zone of residents (living space such as housing sites), including a restricted area located within a 10-km radius from the FDNPS, immediately after r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 21 publications
(28 reference statements)
1
28
0
Order By: Relevance
“…S1). In our previous report, the effectiveness of removing topsoil for decontamination, and the positive relationship between soil radioactivity and air dose rates have been reported previously 16 . One report suggested that the total 137 Cs content in soils was 1200 Bq/kg on average (value range: 20-4400 Bq/kg), which was an 80% decrease from the values determined before the decontamination within agricultural fields in Tomioka Town 19 .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…S1). In our previous report, the effectiveness of removing topsoil for decontamination, and the positive relationship between soil radioactivity and air dose rates have been reported previously 16 . One report suggested that the total 137 Cs content in soils was 1200 Bq/kg on average (value range: 20-4400 Bq/kg), which was an 80% decrease from the values determined before the decontamination within agricultural fields in Tomioka Town 19 .…”
Section: Discussionsupporting
confidence: 66%
“…One car-borne survey in the difficult-to-return zone of Namie Town near Tomioka Town (within the 20 km of the FDNPS) reported absorbed dose rates ranging from 1 to 5 μGy/h in 2017 15 . Our previous handheld measurements showed the median dose rate was 2.3 µSv/h in the difficult-to-return zone of Tomioka Town in 2017 16 .…”
Section: Discussionmentioning
confidence: 96%
“…Limitations of the present study are that the bias associated with the D-SHUTTLE dosimeter positions (investigator) and temperature may be significant; in the present study, the temperature was observed to vary from 17 to 19 °C in October 2019, and from 10 to 13 °C in December 2019 40,41 . In addition, we did not characterize the soils along the Mt Okura hiking trail, although the findings of our previous study showed that dose-forming artificial radiocesium was prevalent in all surface soil samples (0-10 cm) collected in Tomioka Town in 2017 20 . However, in the present study, we used the RADI-PROBE for high and sensitive gamma-ray detection (typically 1400 cps per µSv/h for 137 Cs) 24,25,42 .…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, the reduction of radiocesium was estimated to be only 0.35% from October to December 2019 (Supplementary S2) 26,27 . Thus, the median ambient dose rates along the Mt Okura hiking trail remained relatively stable in 2019 20,24 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation